Intradermal Testing With COVID-19 mRNA Vaccines Predicts Tolerance - Stehlin, Florian; Mahdi-Aljedani, Rima; Canton, Loris; Monzambani-Banderet, Véronique; Miauton, Alix; Girard, Cedric; Kammermann, Kevin; Meylan, Sylvain; Ribi, Camillo; Harr, Thomas; Yerly, Daniel; Muller, Yannick D. (Frontiers in Allergy, 2022)
Background: The newly developed mRNA-based COVID-19 vaccines can provoke anaphylaxis, possibly induced by polyethylene glycol (PEG) contained in the vaccine. The management of persons with a history of PEG allergy, or with a suspected allergic reaction after the first dose remains to be defined. Methods: In this real-life study, we defined two cohorts of individuals: one pre-vaccination including 187 individuals with high-risk profiles for developing anaphylaxis, the second post-vaccination including 87 individuals with suspected allergic reactions after COVID‐19 mRNA vaccine. Upon negative skin test with an mRNA vaccine, a two-step (10%-90%) vaccination protocol was performed. Positive skin tests were confirmed with basophil activation test (BAT). Results: Among 604’267 doses of vaccine, 87 suspected allergic reactions (5 after the booster) were reported to our division for further investigations: 18/87 (21%) were consistent with anaphylaxis, 78/87 (90%) were female, and 47/87 (54%) received the BNT162b2 mRNA vaccine. Vaccine skin tests were negative in 96% and 76% in the pre- and post-vaccination cohorts, respectively. A two-step vaccination was tolerated in 232/236 (98%) of individuals with negative tests. Four individuals experienced isolated asthmatic reaction during the two-step challenge. Vaccine-positive skin tests were consistently confirmed by BAT; CD63 and CD203c expression was selectively inhibited with ibrutinib, suggesting an IgE-dependent mechanism. Conclusion: Sensitization to SARS-Cov2 mRNA vaccines can be detected with intradermal testing. Significantly more individuals were sensitized to mRNA vaccines in the post-vaccination cohort. A two-step 10%-90%-vaccination protocol can be safely administered upon negative skin testing.